IMPLEMENTASI GAMES EDUCATION KAHOOT! TERHADAP HASIL BELAJAR HARMONI PADA PROGRAM STUDI PENDIDIKAN MUSIK UNJ - Hardiarini, Caecilia (Program Studi Pendidikan Musik, 2021)
This study aims to test whether there is an effect of the Kahoot! on the learning outcomes of Harmony. The population in this study were students of the Music Education Study Program at the State University of Jakarta which consisted of 72 students with a sample of 66 students. The results showed that the average final result with the control class was 78.85 with a standard deviation of 5.076. While the average final result in the experimental class is 83.55 with a standard deviation of 4.206. Furthermore, from the test results that are known in the independent sample test table is equal to 0.000. This value indicates that the value is <0.05, so that the difference in results between the experimental group and the control group can be ignored. Based on these results, it can be concluded that there is an influence on the implementation of the education Kahoot! on student learning outcomes on the Harmonies material for semester 112 at 2020.